A Circular Polarized Rectenna with Out-of-Band Suppression for Microwave Power Transmission. (13th November 2016) - Hong, Weijun; Cao, Yanjie; Deng, Li; Li, Shufang; Li, Mengmeng; Liu, Hongjie
Abstract : A novel circular polarized rectenna with out-of-band suppression is proposed in this paper. The circular polarization is realized by corner perturbation on a rectangular radiation patch and enhanced by a diagonal slim slot etched at the center of the patch. An open stub connecting to the quarter wavelength impedance transformer is used to suppress out-of-band wave through harmonics notching. The results of simulations and experiments agree very well, which show that the rectenna obtained −19 dB return loss at 2.4 GHz and −15.5 dB, −18.1 dB, and −11.4 dB suppression on second, third, and fourth harmonic frequency bands, respectively. The reflection coefficient in overall out-of-band, up to 10 GHz, is limited up to −3 dB. Integrated with a voltage doubling rectification circuit, the proposed rectenna can obtain 75.5% RF-to-DC conversion efficiency.